On the Question of the Semantic Understanding of the Cartoon by Preschoolers - Vladimir S. Sobkin; Irina A. Ryabkova; Nadezhda E. Antufueva; Mariya S. Sokolova (Национальный психологический журнал)
Background. Watching cartoons occupies one of the leading places in the leisure time of preschoolers. At the same time, both in our country and abroad, there is a shortage of research on children's perception of this type of art. In this regard, the need for a deeper study of this issue and the analysis of the semantic perception of cartoons at preschool age becomes particularly relevant. Objective. The work is aimed at identifying the specifics of preschoolers' perception and articulation of the basic idea of the cartoon. Study Participants. The study involved 60 children aged 5 to 7 years (from 60 months to 86 months; M = 72.3, SD = 7.63): 30 boys (from 60 months to 86 months; M = 73.3, SD = 7.94) and 30 girls (from 62 months to 86 months; M = 71.3, SD = 7.31), attending kindergartens with the general educational programme. Methods. A half-structured in-depth interview with open questions was applied. The cartoon directed by V. Samsonov “The Old Toy” (1971, running time: 9:42) was used as the research material. The script was written by V. Livanov. Results. 1. The children's answers show that the rationale for the emotional experience after watching the cartoon is based on the assistance to the characters or on the reflected reaction to the actions of another character. 2. The preschoolers’ choice of the favorite episode is based on the emotional experiences that a child has while watching a movie. 3. When defining the main character, children tend to emphasize either his place in the narrative, or his function in the development of the plot, or the emotional dominant that turns out to be associated with the character in the perception of the cartoon. Conclusions. Applying the method of including the theme of children's play in the fabric of the artwork significantly affects the substantive features of the child-viewer's experience of the moral and ethical conflict in the cartoon. The children’s responses indicate the difficult experiences related to the inclusion of both their everyday reality and game reality in the cartoon narrative. Meanwhile, if the questions about specific characters (events) are posed to the child or if they refer to the child's personal experiences, the answers of many preschoolers indicate a fairly deep insight into the meanings of the artwork.